Morphometric and biochemical contributions to the structuration and systematics of the Holm oak Quercus ilex L. specific complex - Lebreton, P; Barbero, M; Quezel, P (ACTA BOTANICA GALLICA, 2001)
The ecological amplitude and the biological variability of the Holm oak are such that any systematic characterization is hazardous. This study, conducted from eleven origins representative of the Western Mediterranean area, is novel by its pluridisciplinary and statistical approach. Chemical (foliar flavonoids) and morphometric data (dry weight, lengthening, veins of the leaves) support the same conclusion that the ``variability{''} of the Holm oak is structured by Ford sensu polymorphism. The distinction between ilex and rotundifolia remains pertinent from a first order perspective, but the second taxon should also be sub-divided into two distinct entities, the first in the Iberian peninsula, the other in North Africa. We consider the Holm oak as a specific complex comprising three taxa: ilex L.; rotundifolia emend. and maghrebiana subsp. nov. Although the Pyrenees constituted a barrier between ilex and rotundifolia, hybridisations and mutual introgressions doubtless explain certain abnormalities in Catalonia and Languedoc, A primarily morphometric determination key is proposed, though to be entirely rigorous only a population-based and multivariate-based approach, with inclusion of the biochemical parameters, can hope to address with sufficiently subtlety a problem of this complexity.
Keywords: Holm oak; Polymorphism; systematics